2020
DOI: 10.3390/ijerph17249185
|View full text |Cite
|
Sign up to set email alerts
|

Work Ability among Upper-Secondary School Teachers: Examining the Role of Burnout, Sense of Coherence, and Work-Related and Lifestyle Factors

Abstract: Maintaining and promoting teachers’ work ability is essential for increasing productivity and preventing early exit from the teaching profession. This study aimed to identify the predictors of work ability among upper-secondary school teachers and examine the mediating role of burnout. A large and diverse group of Czech upper-secondary school teachers was surveyed to address this goal. The sample comprised 531 upper-secondary school teachers (50.0 ± 9.94 years, 19.9 ± 10.62 in the teaching profession, 57.6% fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 113 publications
0
12
1
Order By: Relevance
“…However, this research identified that, in more advanced courses (or as the teaching experience of the faculty members increases), the evaluation of the characteristics in which teaching is carried out is minimized, and the teaching itself is more highly valued. This contradicts previous studies that indicate that the capacity to adapt to new scenarios decreases with age due to physical and mental exhaustion, which appears more prematurely than in previous decades [19,20].…”
Section: Discussioncontrasting
confidence: 95%
“…However, this research identified that, in more advanced courses (or as the teaching experience of the faculty members increases), the evaluation of the characteristics in which teaching is carried out is minimized, and the teaching itself is more highly valued. This contradicts previous studies that indicate that the capacity to adapt to new scenarios decreases with age due to physical and mental exhaustion, which appears more prematurely than in previous decades [19,20].…”
Section: Discussioncontrasting
confidence: 95%
“…In addition, in the educational field, teachers must face a complex reality and multiple scenarios (Valentino & Sosnowski, 2019). The ability to cope with all these problems in a resilient manner appears to be a key factor in the prevention of work-related stress (Hlaďo et al, 2020). Among other factors, gender could be involved in the development of resilient behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Teacher job experience is an integral element in determining teaching efficacy as studies revealed that more experienced teachers are inclined to bridge the gap between work and time off [63][64][65]. Generally speaking, students' increased outcome, attendance, and overall success in school are linked to teaching experience in the United States, indicating that for most teachers an increase in experience results in more efficiency that benefits not just the teacher's students but the school as a community [66].…”
Section: Inclusive Education Practices and Teachers' Sociodemographic Characteristicsmentioning
confidence: 99%